A Pictorial Record of the Qing Dynasty : Qing Dynasty Architecture - Peking University Library 652375; Gale Group (Online service) 651863 (Singapore : Cengage Learning Asia Pte. Ltd., 2010)
Features a visual reference for researching the architectural evolution during the Qing Dynasty and also provides a multi-faceted perspective on China's political, social, cultural, and economic landscapes then.